SCADA Learning Trainer Development for Vocational High School Electrical Engineering Teachers in Semarang - Supraptono, Eko; Wibowo, Apriansyah; Andrasto, Tatyantoro; Arief, Ulfah Mediaty; Sukamta, Sri; Ekarini, Fitria; Baskoro, Aldo Luhung; Qunefi, Fuat; Mubarak, Raihan Fa'iq; Fathimah, Aisya (Jurnal Penelitian Pendidikan, 2025)
One of the most important things that support an effective learning process is the ability of educators to create learning media. The ability to make trainers or teaching aids that support theoretical and practical learning is very important, especially for Vocational High Schools (SMK) teachers in electrical engineering. The purpose of this community service project is to prepare electrical engineering teachers to make Supervisory Control and Data Acquisition (SCADA) trainers suitable for use in the Solar Power Plant (PLTS) curriculum. Fifty teachers from Nurul Baqi Vocational High Schools in Semarang participated in the training for 40 lesson hours delivered with a Project Based Learning (PjBL) approach. The training results showed an increased understanding and application of the SCADA system by the participants, especially in terms of measuring current, voltage, solar radiation, temperature, as well as.